Consumption and preference rates of the various larval stages of Allograpta exotica as biological control agents of Myzus persicae and Frankliniella gemina - Maza, Noelia; Páez Jerez, Paula Gabriela; Bressán, Emilse; Funes, Claudia Fernanda; Kirschbaum, Daniel Santiago (Wiley, 2024)
Fruit and vegetable crops are affected by numerous arthropods, including aphids and thrips. Hoverfly adults are important pollinators, and their larvae are mainly aphid predators. Molecular studies on the stomach contents of larvae allowed to associate hoverflies with the consumption of other soft-bodied arthropods, including thrips, with few records found in Neotropical hoverfly species. Allograpta exotica (Wiedemann) (Diptera: Syrphidae), a species widely distributed in the Americas, from the USA to Argentinian Patagonia, has been associated with numerous crops mainly affected by aphids, and to a lesser extent with whiteflies. The objective of this work was to assess the consumption and preference rates of various instars of A. exotica as biocontrol agents for two major insect pests, Myzus persicae (Sulzer) (Hemiptera: Aphididae) and Frankliniella gemina (Bagnall) (Thysanoptera: Thripidae), under controlled laboratory conditions. Additionally, we morphologically characterized the three larval stages of A. exotica. We determined that all three instars of A. exotica consume both M. persicae and F. gemina, and that they kill more thrips than aphids. Still, A. exotica preferred M. persicae over F. gemina, even when the relative aphid availability decreased compared to F. gemina, although consumption of both prey types remained high. Interestingly, A. exotica second instars consumed four times more thrips than aphids. This study explored the potential use of one of the most common hoverfly species in fruit and vegetable crops as a biocontrol agent of aphids and thrips. Further laboratory and field studies should explore more deeply the potential of this Neotropical beneficial dipteran.